Agronomics and ecology of wheat-based cropping systems: unveiling dynamics for sustainable agriculture - Simão, Luana Machado (Kansas State University, 2024)
Wheat (Triticum aestivum L.) area has dramatically reduced in major wheat-producing nations such as the United States, Canada, China, and Turkey. This reduction is primarily attributed to the expansion of more attractive crops such as maize (Zea mays L.) and soybean (Glycine max (L.) Merr.). Decreasing wheat area poses risks in regions where wheat is a staple, given its multitude of benefits and ecosystem services to cropping systems. Furthermore, introducing wheat into rotations in areas where it hasn't historically been a major crop could yield substantial advantages for overall sustainability and productivity. Our overarching goal was to evaluate the benefits and challenges of maintaining wheat in more intensified cropping systems. Our specific goals were to: (i) outline benefits of adding wheat to simple crop rotations (i.e., one to three rotational crops) by reviewing ca. 300 peer-reviewed studies worldwide; (ii) examine the long-term (44-yr) application of conservation agriculture principles (i.e., minimal soil disturbance, crop rotation, and permanent soil cover) on grain yield, yield stability, and adaptability of winter wheat, soybean, and grain sorghum (Sorghum bicolor (L.) Moench); and (iii) evaluate the impact of intensification of cropping systems and nitrogen (N) management on the wheat phase of the system. In our review to address the first objective, we highlighted the wheat’s versatility for tactical in-season crop management [e.g., flexible sowing dates, crop type (winter vs. spring), and N fertility] and strategic cropping system management (e.g., grazing and double-cropping) and provided evidence supporting the positive impact of wheat on the grain yield and yield stability of other rotational crops. The introduction of wheat to simple crop rotations can (i) interrupt pest population cycles by serving as a break crop; (ii) decrease N application requirements, thus reducing N losses, greenhouse gas emissions, soil acidification, and production costs; (iii) improve soil health and carbon sequestration; (iv) increase resource use-efficiency of the cropping system; (v) foment fauna populations, and (vi) decrease variability in economic returns. In response to our second objective, we summarized results from a long-term (1973 – 2018) field experiment near Ashland Bottoms, KS that evaluated three tillage systems (no-till, reduced till, and conventional till) and five 2-yr crop rotations (continuous winter wheat, soybean, and grain sorghum; and soybean-grain sorghum and soybean-winter wheat). Crop rotation consistently out-yielded continuous cropping and the advantage was enhanced when integrated with no-till. Wheat was adaptable to low- and high-yielding environments with similar grain yield and yield stability among treatments, except for no-till continuous wheat, which had the lowest yield stability and grain yield (2.5 vs. 3.5 Mg ha⁻¹). Soybean grown after wheat was more adaptable to low-yielding environments and grown after sorghum to high-yielding environments. To answer our third objective, a field experiment near Ashland Bottoms, KS, evaluated sixteen combinations of three N-management strategies (Green N, Standard, and Progressive) and nine crop sequences. Green N did not receive external N supply and it was implemented in a rotation constructed to supply N through biological fixation from previous legume crop. Standard consisted of a baseline N-management, while Progressive was an intensified N-management where all “4R” (right rate, time, source, and placement) were simultaneously improved. Crop sequences were either Grain Only or Dual-Purpose systems with different levels of intensification. Both standard and progressive N management practices had similar results within crop sequences, but Green N decreased dual-purpose winter wheat grain yield and shoot biomass. Cropping systems that allowed winter wheat to be sown at the optimum date had the greatest yields. Later sowing dates were most likely to reduce plant available water at sowing, mainly when following a summer crop, and could delay wheat’s development resulting in higher temperatures during the critical period for yield determination (i.e., the days surrounding anthesis) and shorter grain filling duration. Results from this research highlight that wheat offers unique opportunities to increase diversification and foster more sustainable and resilient agroecosystems.
Keywords: Wheat; Crop rotation; Cropping system; Nitrogen; Tillage; Sustainability